2018
DOI: 10.1089/neu.2017.5284
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Traumatic Brain Injury with Vepoloxamer (Purified Poloxamer 188)

Abstract: Vepoloxamer is an amphipathic polymer that has shown potent hemorrheologic, cytoprotective, and anti-inflammatory effects in both pre-clinical and clinical studies. This study was designed to investigate the therapeutic effects of vepoloxamer on sensorimotor and cognitive functional recovery in rats after traumatic brain injury (TBI) induced by controlled cortical impact. Young adult male Wistar rats were randomly divided into the following groups: 1) sham; 2) saline; or 3) vepoloxamer. Vepoloxamer (300 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…It has been reported that two types of injuries are typically associated with TBI: mechanical injury, which is an irreversible injury, and secondary injury (or non-mechanical injury), which is reversible. The secondary injury begins after the primary injury, regulates various cascades, and activates neuronal apoptosis and dysfunction ( Zhang et al, 2018 ). Oxidative stress is mainly caused by secondary injury, which plays a contributing role in the oxidation of macromolecules and neuronal dysfunction following TBI pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that two types of injuries are typically associated with TBI: mechanical injury, which is an irreversible injury, and secondary injury (or non-mechanical injury), which is reversible. The secondary injury begins after the primary injury, regulates various cascades, and activates neuronal apoptosis and dysfunction ( Zhang et al, 2018 ). Oxidative stress is mainly caused by secondary injury, which plays a contributing role in the oxidation of macromolecules and neuronal dysfunction following TBI pathology.…”
Section: Discussionmentioning
confidence: 99%
“…TBI was induced by a controlled cortical impact device with minor modifications in our laboratory ( Zhang et al, 2018 ; Edward Dixon et al, 1991 ). In brief, the experimental rats were anesthetized (75 mg/kg b.wt.…”
Section: Methodsmentioning
confidence: 99%
“… 109 , 110 Acute (initiated 30 min post injury) or delayed (initiated 9 months post injury) treatment with anatabine that has putative anti-inflammatory actions improves long-term spatial memory and reduces pathological sequelae at late time-points in mice after repetitive mTBI. 111 These studies show that neuroinflammation may be an important manipulatable aspect of secondary injury in animal 75 , 96 , 97 , 112 and human TBI. 58 , 113 , 114 However, the use of general anti-inflammatory drugs has not worked effectively for TBI.…”
Section: Neuroinflammationmentioning
confidence: 87%
“…Chronic traumatic brain inflammation manifested by extensive microglial and astroglial activation may be the most important cause of post-traumatic neurodegeneration including CTE. 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 Neuroinflammation is associated with greater p-Tau pathology in CTE. 104 The potential key role of increased neuroinflammation in CTE development and progression suggests that inflammatory molecules may serve as important diagnostic or predictive biomarkers as well as promising therapeutic targets in CTE.…”
Section: Neuroinflammationmentioning
confidence: 98%
“…Synthetic membrane stabilizers may ultimately extend to numerous other inherited or acquired diseases in which cell membrane integrity is compromised. In the last few years, many preclinical studies using P188 as cell membrane stabilizers have been published in a variety of pathological settings, including amyotrophic lateral sclerosis [ 201 ], traumatic brain injury [ 202 ], aggregation of unfolded protein [ 203 207 ], hypoxia and ischemia-reperfusion injury [ 154 , 208 , 209 ], irradiation and burn injury [ 152 , 210 , 211 ], cartilage damage, and joint degeneration following blunt impact [ 212 214 ]. Based on the potential novel uses of copolymer-based membrane stabilizers in various other diseases where the cell membrane is damaged, one could anticipate that increased academic and clinical interest in this therapeutic strategy will help promote faster translation to human clinical applications.…”
Section: Discussionmentioning
confidence: 99%